The Positivisation of National Sharia Board Fatwa About Mudaraba Into Financial Service Authority Regulation - Nur Hasanah (Universitas Islam Negeri Jakarta, 2018)
The positivisation of National Sharia Board (DSN) fatwa about mudaraba into Financial Service Authority (OJK) regulation is an effort which conducted by OJK in running it’s regulating such as arranged in the Law Number 21 of 2011 regarding OJK. With this positivisation, DSN fatwa has legal and binding power because getting inside regulation such as arranged in the Law Number 12 of 2011 regarding the Establishment of Legislation (P3). However, there are gap and the difference content between the provisions in DSN fatwa above with OJK regulation by dint of positivisation pattern. Moreover, although there is DSN fatwa content which has not been asorbed in to OJK regulation, but it still has legal and binding power in shari’a financial industry in case reviewed from the perspective of H.L.A Hart’s legal theory.